2020
DOI: 10.3390/journalmedia1010005
|View full text |Cite
|
Sign up to set email alerts
|

Saving Lives and Changing Minds with Twitter in Disasters and Pandemics: A Literature Review

Abstract: Twitter is a major tool for communication during emergencies and disasters. This study aimed to investigate Twitter use during natural hazards and pandemics. The included studies reported the role of Twitter in disasters triggered by natural hazards. Electronic databases were used for a comprehensive literature search to identify the records that match the mentioned inclusion criteria published through May 2020. Forty-five articles met the selection criteria and were included in the review. These indicated ten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…They observed that Twitter is useful in enhancing the social capital of the health sector (Tang et al ., 2018), predicting disease outbreaks (Charles-Smith et al ., 2015) and forecasting the dynamics of outbreaks (Nsoesie et al ., 2014). It was indicated that Twitter, when used during disasters, can provide useful information to various stakeholders and is a good tool for sharing information (Abedin et al ., 2014; Martínez-Rojas et al ., 2018; Seddighi et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They observed that Twitter is useful in enhancing the social capital of the health sector (Tang et al ., 2018), predicting disease outbreaks (Charles-Smith et al ., 2015) and forecasting the dynamics of outbreaks (Nsoesie et al ., 2014). It was indicated that Twitter, when used during disasters, can provide useful information to various stakeholders and is a good tool for sharing information (Abedin et al ., 2014; Martínez-Rojas et al ., 2018; Seddighi et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an increasingly connected and digital world, affected communities become a valuable source of relevant information [41]. Authors and SMEs have explored the use of an evolved medical intelligence platform (MIP) supported by the Expert.ai Cogito engine [4], able to processes, in addition to scientific literature, national and local press, tweets and other social media data [42][43][44][45] available on the surface, deep and dark web [42,46,47].…”
Section: Medical and Security Threats Analysismentioning
confidence: 99%
“…This is due to the quantity of data shared every day by millions, and the impact of tweets from institutions and influencers on their followers (Murthy, 2018). Twitter can be utilised for safeguarding against medical threats due to its speed and possibility to disseminate information in emergencies and disasters preparation (Seddighi et al, 2020), to send warnings and identify needs and required responses. Its reach makes it also an ideal platform for planning and preparedness coordination (Kusumasari, et al, 2020).…”
Section: Twittermentioning
confidence: 99%